Airlift bioreactor system for simultaneous removal of hydrogen sulfide and ammonia from synthetic and actual waste gases. Issue 8 (3rd July 2018) - Chen, Chih-Yu; Tsai, Teh-Hua; Chang, Chih-Hao; Tseng, Chih-Fang; Lin, Shih-Yun; Chung, Ying-Chien
ABSTRACT: The effectiveness of an airlift reactor system in simultaneously removing hydrogen sulfide (H2 S) and ammonia (NH3 ) from synthetic and actual waste gases was investigated. The effects of various parameters, including the ratio of inoculum dilution, the gas concentration, the gas retention time, catalyst addition, the bubble size, and light intensity, on H2 S and NH3 removal were investigated. The results revealed that optimal gas removal could be achieved by employing an activated inoculum, using a small bubble stone, applying reinforced fluorescent light, adding Fe2 O3 catalysts, and applying a gas retention time of 20 s. The shock loading did not substantially affect the removal efficiency of the airlift bioreactor. Moreover, more than 98.5% of H2 S and 99.6% of NH3 were removed in treating actual waste gases. Fifteen bands or species were observed in a profile from denaturing gradient gel electrophoresis during waste gas treatment. Phylogenetic analysis revealed the phylum Proteobacteria to be predominant. Six bacterial strains were consistently present during the entire operating period; however, only Rhodobacter capsulatus, Rhodopseudomonas palustris, and Arthrobacter oxydans were relatively abundant in the system. The photosynthetic bacteria R. capsulatus and R. palustris were responsible for H2 S oxidation, especially when the reinforced fluorescent light was used. The heterotrophic nitrifier A. oxydans was responsible for NH3 oxidation. To our knowledge, this is the first report on simultaneous H2 S and NH3 removal using an airlift bioreactor system. It clearly demonstrates the effectiveness of the system in treating actual waste gases containing H2 S and NH3 .